The effects of double antibiotic paste and amoxicillin-clavulanate paste used in endodontic regeneration on microhardness of radicular dentine: An In vitro study - Meenu Madhukumar; Praveena Geetha; K Radhakrishnan Nair; Manu Unnikrishnan (Wolters Kluwer Medknow Publications, 2021)
Objective: Double antibiotic paste is a root canal medicament used in regenerative endodontics and its long-term exposure to dental hard tissues was shown to reduce its mechanical properties. The amoxicillin-clavulanate paste is a medicament effective against endodontic pathogens and is effective in endodontic regeneration. Its effect on radicular dentine is yet to be investigated. The purpose of this study is to investigate and compare the effects of double antibiotic paste and amoxicillin-clavulanate paste on the microhardness of radicular dentine. Materials and Methods: The root canal of 45 premolars was mechanically prepared and divided into three groups for the placement of intracanal medicament: Group 1 (n = 15) double antibiotic paste, Group 2 (n = 15) amoxicillin-clavulanate paste, and Group 3 control group (n = 15). All the specimens were subject to microhardness testing at 500 and 1000 microns depth for 1 week, 1 month, and 3 months and analyzed. Results: There is no significant reduction in microhardness of radicular dentin at 1 week on all the three groups. At 1 month and 3 month period, the amoxicillin-clavulanate paste is found to have no significant effect on dentin microhardness when compared to double antibiotic paste. Conclusion: The use of amoxicillin-clavulanate paste as an intracanal medicament does not cause significant weakening of dentin even after its long-term use.